2007
DOI: 10.1111/j.1748-5827.2007.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulinoma in a cat

Abstract: A 14-year-old domestic shorthair cat was presented with hypoglycaemia and seizures of several weeks duration. Bloodwork revealed hypoglycaemia (1.83 mmol/l; reference range 4.22-8.05 mmol/l) with concurrent normal insulin levels (171 pmol/l; reference range 72-583 pmol/l). An insulinoma was suspected and medical and dietary management were attempted with minimal success. An exploratory laparotomy was performed and a single, well-defined mass was found within the left lobe of the pancreas. The mass was removed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 7 publications
4
59
0
Order By: Relevance
“…Insulinoma is an uncommon tumor of cats. Previous reports of feline insulinoma have focused on clinical and histological features of these tumors 1–5 . In the current study, immunohistochemical analysis demonstrated the production of multiple peptide hormones by the tumor cells.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Insulinoma is an uncommon tumor of cats. Previous reports of feline insulinoma have focused on clinical and histological features of these tumors 1–5 . In the current study, immunohistochemical analysis demonstrated the production of multiple peptide hormones by the tumor cells.…”
Section: Discussionmentioning
confidence: 58%
“…Insulin expression in feline insulinomas, however, is variable and has been described as patchy to diffuse, 2,4,10 with >50% of cells staining insulin‐positive in some tumors 2 and no insulin staining reported in 1 tumor 1 . Despite the apparent variation in tumor insulin production, the hypoglycemia and hyperinsulinemia that characterize the clinical presentation of cats with insulinoma indicate that tumor cells retain the capacity for insulin release 1–5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin-secreting beta-cell tumors are rare in cats with only a few single cat case reports in the literature (McMillan, 1985;O'Brien et al, 1990;Hawks et al, 1992;Kraje, 2003;Greene and Bright, 2008) and one additional report in which the beta-cell tumor was an incidental finding at necropsy in a cat with ductal pancreatic adenocarcinoma (Carpenter et al, 1987). We have seen only two cats with beta-cell neoplasia during the past three decades, in contrast to more than 150 dogs with the disease during the same time interval.…”
Section: Insulin-secreting Beta-cell Tumors In Catsmentioning
confidence: 99%
“…9 The age of onset may have provided a clue to this non-neoplastic disease, as this cat was much younger than all previously reported cases of feline insulinoma (all were >12 years of age at diagnosis). 10,11 …”
Section: Discussionmentioning
confidence: 99%